STRATEGI PENGEMBANGAN FASILITAS DI RUANG AUDIO VISUAL MUSEUM BENTENG VREDEBURG YOGYAKARTA - , DAHLIA MUTIA DEWI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to analyze the implementation of the development strategy SWOT analysis (Strength, Weaknesses, Opportunities, Threats) as a development strategy at the Audio Visual Room Museum Vredeburg Yogyakarta by analyzing in terms of strengths, weaknesses, opportunities and threats. This study is expected to provide input on Vredeburg Museum. The existence of the audio visual room has not been able to provide satisfaction for the visitors, while the audio-visual room is very important for the progress of the museum. The potential that exists in the audio-visual room includes buildings that have colonial architecture building concept is the main attraction of visitors, audio visual room has a very small form, the conditions there are various facilities damage but there are limited facilities and infrastructure that are less attrac tive to visitors entering the space audiovisual therefore the authors have added strategy development strategy is the latest film and more innovative, making the efficiency of the screening time, replace any damage in the audio-visual room, utilizing the upstairs exhibition space as a means of expanding the room.